Pengelolaan Keuangan Keluarga pada Ibu-Ibu Kelompok HALMI Al-Mudzakir - Fikri Farhan (Universitas Mathla'ul Anwar Banten, 2021)
FAMILY FINANCIAL MANAGEMENT FOR MEMBERS OF HALMI AL-MUDZAKIR. Family financial management is one way to achieve sakinah (peace) in the family. Generally, conflicts in the household originate from financial problems. The majority of financial managers in the family are housewives. So that training in family financial management for them is essential. This community service aims to provide training in family management to the members of the HALMI group in Plosokuning, Ngagklik. The service was carried out in two methods, the lecture method and the training, which contained the importance of financial management for the family, basics of sakinah financial, and the practice of making a family balance sheet. Partners are given training on how to create a family financial position and how to interpret it. The output of this service is that the mothers of the HALMI group can manage their family finances. Thus, they can achieve financial peace.